Individualized Homeopathy for Depression in Climacteric Women: Comments on the Retraction by PLoS ONE - Macías-Cortés, Emma del Carmen; Llanes-González, Lidia; Aguilar-Faisal, Leopoldo; Asbun-Bojalil, Juan (Homeopathy, 2020)
In April 2020 PLoS ONE retracted an original clinical research article, published in 2015, in which we demonstrated that individualized homeopathic treatment improves depression symptoms in climacteric women. The original assessment of this study was carried out by an expert in psychiatry (depression research) with close to 35 years' experience in the field of mental health. During post-publication discussions, no serious breaches of scientific procedure or misconduct were even insinuated. Our team answered all “points of concern”, raised by the current PLoS ONE editors, in extensive detail. All these were potential limitations of our study, which would usually be addressed by one of several appropriate post-publication actions, ranging from discussion of the concern within a systematic review, through to correcting the study itself by adding a correction notice. Therefore, in the interests of transparency and accuracy, a summary of the most relevant points is provided, so that a fair-minded reader can objectively form a clear opinion.
Keywords: individualized homeopathy; retraction; depression; randomized controlled trial